Cardinal temperatures of seed germination of Brucea javanica (L.) Merr. and its physiological respons on the seed drying - HADI SUTARNO; NING WIKAN UTAMI (Society for Indonesian Biodiversity, 2007)
The slow and low germination rate of Brucea javanica makes constraint in its plant utilization and development. Research on cardinal temperatures (temperature of minimum, optimum and maximum) of germination; and the effect to know how the physiologycal respons on seed drying. It is important in activities of agronomy, adaptation and domestication; sofar applicable on forestation and ex-situ conservation. Based on seed germination observation on thermogradientbar with range from 2 to 550C, the minimum temperature and optimum temperature of germination were found 30,40C, by germination rate at least 50% for 19 days period; and the maximum temperature was 33,70C, by at least 50% for 25 days period. The seed respons on drying as approach the recalsitrant study was discussed.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: cardinal temperatures, germination,Brucea javanica, seed drying.